Lesser prairie-chicken movement, space use, survival, and response to anthropogenic structures in Kansas and Colorado - Plumb, Reid Thomas (Kansas State University, 2015)
The lesser prairie-chicken (Tympanuchus pallidicinctus) is an endemic North American prairie grouse once widely distributed in the southwestern Great Plains. Recent population declines and continued threats to lesser prairie-chicken populations prompted the U.S. Fish and Wildlife Service to list the species as “threatened” under the protection of the Endangered Species Act of 1973 in May 2014. The northern extent of the species range in Kansas and Colorado supports 2/3 of the remaining range-wide population of lesser prairie-chickens, but has thus far been relatively understudied. Concern for species viability has created a need to fill current knowledge gaps in lesser prairie-chicken ecology, provide more recent demographic information, and develop appropriate conservation actions. I evaluated female survival, movement, space use, and effects of anthropogenic features during the breeding seasons of 2013 and 2014. I captured and radio-tagged 201 females with satellite GPS (N = 114) and VHF (N = 82) transmitters within the three ecoregions of Kansas and Colorado. Mean daily movement varied by region, year, and breeding season period but the amount of space used was consistent between ecoregions and years. On average, females moved 1352 m ± 12 [SE] per day. Females moved the greatest distances during the lekking period of the breeding season with females moving 2074 m ± 36 per day. Females were most sedentary during the brooding period moving only 780 m ± 14 per day. Mean breeding season home range size was estimated to be 340 ha ± 27. The lekking period had the greatest amount of movement as a result of females visiting leks to find mates, copulate, and search for nest locations. Female’s movements were reduced during the brooding period because of physical limitations of the brood mobility. Variation in movement between ecoregions was most likely a product of fragmentation as females moved 10-30% more in northwest Kansas compared to the study sites, which was characterized by northwest Kansas having the greatest degree of fragmentation. Survival varied by ecoregion with females in northwest Kansas having the lowest probability of surviving the 6-month breeding season compared to other ecoregions. Estimated 6-month breeding season survival during 2013 and 2014 was 0.455 (95% CI = 0.38 – 0.53). Survival was lowest during the nesting period, which claimed 59.5% of all observed mortalities. Survival increased from 2013 to 2014 in northwest Kansas as grassland habitats recovered from extreme drought conditions in 2013. Drought was less severe in south-central Kansas and survival rates remained fairly consistent across years. Avian and mammalian predators caused 45.7% and 34.3% of breeding season mortalities, respectively. Other mortalities were either cause by snakes or were unknown (5.7%, 14.3%). Overhead cover may have been limited from drought conditions causing nesting females to be more visible to avian predators during incubation. When pooled across years and ecoregions, rump-mounted GPS transmitters did not adversely affect female survival when compared to commonly used necklace style VHF transmitter (VHF: 0.48 95% CI = 0.39 – 0.58; GPS: 0.50 95% CI = 0.38 – 0.64). Distance to distribution power lines and lek were significant predictors of female space use within their home range with females behaviorally avoiding distribution power lines and using space closer to leks. Space use decreased with increasing oil well density. Females avoided areas that had well densities of 23 wells/250 ha. Observed female locations were further from anthropogenic features but closer to leks on average than at random. Avoidance behavior of anthropogenic features may result in functional habitat loss and reduce the amount of suitable habitat available; compounding previously fragmented landscapes. Anthropogenic features may limit movement by acting as barriers on the landscape and potentially disrupt population connectivity. Furthermore, habitats selected for nesting and brooding may result in potential ecological traps because of reduce breeding success when impacted by increased occurrence and densities of anthropogenic features. Reduced breeding success can have significant negative impacts on population persistence. Average home range size across all ecoregions indicated that female lesser prairie-chickens need at least 340 ha of habitat to fulfill her life-history requirements during the breeding season. Brooding habitats need to be in close proximity (≤ 750 m) to nesting cover to reduce distance traversed by newly hatched broods. Reducing grazing pressure will ensure that sufficient vertical habitat structure is available during the nesting period and increase female survival; especially in times of drought. Mangers should restrict construction of anthropogenic features near or within suitable lesser prairie-chicken habitat with emphasis on distribution power lines. Well densities should not exceed 1 well/60 acres (11 wells/section) for a >10% probability of use. However, because the affect that density of wells has on demographic rates of lesser prairie-chickens has yet to be determined, a conservative approach where well densities in or adjacent to grassland patches should be minimized as much as possible is best.
Keywords: Lesser prairie-chicken; Movement; Survival; Anthropogenic impacts; Space use; Tympanuchus pallidicinctus; Biology (0306); Wildlife Conservation (0284); Wildlife Management (0286)